Perancangan Aplikasi Surat Menggunakan Framework Codeigniter Dan Bootstrap Pada LPPM Universitas Mohammad Husni Thamrin - Abu Sopian; Rano Agustino; Agus Wiyatno (Universitas Mohammad Husni Thamrin, 2020)
Currently it is the Era of the Industrial Revolution 4.0, where the industrial sector as well as companies and organizations in various fields are required to change. This change is when information and communication technology is used to reach the highest point in the use of digital technology. The Industrial Era 4.0 has had a rapid impact on all activities carried out in the industrial sector and company organizational organizations. The higher the information and communication technology used, the faster the information delivery process will be. A fast information process can help the smooth running of administrative activities in a company or organization, especially administrative activities related to correspondence activities. In managing incoming and outgoing letters at the Institute for Research and Community Service (LPPM) at Mohammad Husni Thamrin University, currently there are shortcomings that are still stored and recorded in making correspondence. This can result in information being presented too late. It is that the need for a technology that will help of the smooth running of the administration in making correspondence by writing letters at the Institute for Research and Community Service (LPPM) at Mohammad Husni Thamrin University. Making a letter application is done quickly and easily by using UML (Unfied Modeling Language) as a tool that helps analyze the flow of the correspondence system and makes it easier to build applications that are needed as well as in the development process. With the help of MySQL as a database, Bootstrap Framework and using the PHP programming language.Keywords: Design, Letter, UML, Codeigniter, Bootstrap